A Multicultural Study of Suma Budaya Marawis Music Band in Pekalongan - Mujadid, Ahmad Zahry; Sunarto, Sunarto; Utomo, Udi (Catharsis, 2018)
The entity of the adoption process produced a concept of multiculturalism in the form of marawis music presented by Suma Budaya group. This study aims to analyze the musical elements of the group Suma Budaya marawis Pekalongan City and multicultural characteristics in the context of urban Pekalongan. The research method is qualitative with interdisciplinary approach. The supporting data were collected from observation, interview, and documentation. Then, these data were validated using triangulation technique. The analysis of the data included four steps, including data collection, data reduction, data presentation, and conclusion. The results showed that the musical elements presented by the Suma Culture marawis group brought Arabic, Javanese and Chinese concepts in the show, among others realized through (a) the addition of musical instrument that is Javanese gamelan that have elements of pentatonic tones of Java with the pelog nem is 1 (ji), 2 (ro), 3 (lu), 5 (mo), 6 (nem), and when the tone of nog in gamelan make a diatonic tone it will sound 3 (mi), 4 (fa), 5 (sol), 7 (si), 1 (do); (b) Chinese elements can be seen from the Chinese pentatonic tones found in Ghuzeng musical instruments: 1 (do), 2 (re), 3 (mi), 5 (so), 6 (la); (c) Arabic elements in this case can be seen from rampak marawis itself, including with the musical instrument marawis, bass jidor, and darbuka.